My dead friend Zoe [videorecording (DVD)] - Hausmann-Stokes, Kyle, 1982-; Bermudez, A. J., 1987-; Chen, Cherish; Martin-Green, Sonequa, 1985-; Morales, Natalie; Reuben, Gloria, 1964-; Ambudkar, Utkarsh; Freeman, Morgan; Harris, Ed, 1950-; Romer, Dan; Roe, Matt Sakatani (Universal, 2025)
Merit, a U.S. Army Afghanistan veteran is at odds with her family thanks to the presence of Zoe, her dead best friend from the Army. Despite the persistence of her VA group counselor, the tough love of her mother and the levity of an unexpected love interest, Merit's cozy-dysfunctional friendship with Zoe keeps the duo insulated from the world. That is until Merit's estranged grandfather--holed up at the family's ancestral lake house--begins to lose his way and needs the one thing he refuses... help.